Electronic CPA‐Laser Having Enhanced Sensitivity and Tunability - Minye Yang; Lukang Wang; Zhilu Ye; Qi Zhong; Baolong Jian; Xiaohui Zhang; Şahin K. Özdemir; Ming Liu (Advanced Electronic Materials)
Abstract Exceptional point degeneracies, which are spectral singularities of non‐Hermitian systems, have been widely utilized for building optical, mechanical, or electrical sensing systems with much larger responses than those utilizing Hermitian degeneracies. However, such systems suffer from enhanced noise, which negates the enhanced response and thus does not provide any improvement in signal‐to‐noise ratio. Recently, the coherent perfect absorber (CPA)‐laser, which also utilizes non‐Hermitian singularity, has been used in sensing systems resulting in better noise robustness and enhanced responsivity. Nonetheless, CPA‐laser (CPAL) implementation requires all system parameters to be immutable, which hinders progress toward their practical use for sensing purposes. Here, a tunable electronic CPA‐laser is reported that overcomes these obstacles providing ultrahigh sensitivity as validated in the experiments for monitoring arterial pressure and respiration. This CPAL sensing scheme utilizes inductive coupling between gain and loss sub‐components and thereby the whole system can be decomposed into an active reader and a passive sensor, which enables better tunability and performance compared to previously reported CPAL systems. Moreover, the proposed CPAL system exhibits better performance compared to exceptional point‐based systems having a similar circuit structure. This research paves the way for exploring electronic CPAL for sensing applications and may have a profound impact on the next‐generation, ultrasensitive electromagnetic sensing system.